Risk-taking and Self-actualization in EFL Positive Classroom Environment - Liqaa Habeb Al-Obaydi (ELS Journal on Interdisciplinary Studies in Humanities, 2020)
This study expresses a positive classroom environment depending on two axes; physical setting of the classroom and the role of the teacher as a positive atmosphere creator. By applying the proposed environment, the study tries to discover the impact of it on EFL college students’ self-actualization and risk-taking. To obtain the objectives and to verify a hypothesis, an experimental design was applied by using two groups, experimental and control. The sample of the study consists of sixty EFL first stage college students divided into two groups, each of which is thirty. The first group is the experimental, which is taught in a positive classroom environment as stated by this study. The second group is the control one, which is taught traditionally by letting the classroom as it is, without any positive addition. Two measurement tools have been used; a scaled questionnaire that has been adapted from Stephen D. Luft (2007), and a self-actualization scale that is developed by Jones & Crandall (1986).Using a t-test for the two independent samples shows notable effects on EFL college students’ risk-taking and self-actualization. Based on the results obtained, educational implications that are concerned with teachers and students have been put forward.